Decolonizing health in Canada: A Manitoba first nation perspective - Rachel Eni; Wanda Phillips-Beck; Grace Kyoon Achan; Josée G. Lavoie; Kathi Avery Kinew; Alan Katz (BMC, 2021)
Abstract Introduction & Background Global persistence of health inequities for Indigenous peoples is evident in ongoing discrepancies in health and standards of living. International literature suggests the key to transformation lies in Indigenous efforts to control Indigenous health and healthcare. Previous authors have focused upon participation, structural transformation, and culturally appropriate healthcare recognized as a political right as fundamental tenets of Indigenous control. Contextualizing Indigenous health and wellness falls within a growing discussion on decolonization - a resituating of expertise that privileges Indigenous voice and interests. Methods The study is a qualitative, grounded theory analysis, which is a constructivist approach to social research allowing for generation of theory in praxis, through interactions and conversations between researchers and participants. One hundred eighty-three interviews with additional focus groups were held between 2013-15 in eight Manitoba First Nation communities representing different models of health delivery, geographies, accessibilities, and Indigenous language groups. Community research assistants and respected Elders participated in data collection, analysis and interpretation. Line-by-line coding and constant comparative method led to the discovery of converging themes. Findings Ultimately four main themes arose: 1) First Nation control of healthcare; 2) traditional medicine and healing activities; 3) full and meaningful community participation; and 4) cleaning up impacts of colonization. Joint analyses and interpretation of findings revealed substantial evidence that communities were looking profoundly into problems of improperly delivered services and health inequities. Issues were consistent with those highlighted by international commissions on reconciliation, health, Indigenous rights and liberties. To those documents, these findings add ground upon which to build the transformative agenda. Results & Discussion Communities discussed the need for creation of protocols, constitution and laws to ensure growth of a decolonizing agenda. Inclusive to the concept are holistic, preventative, traditional health perspectives, and Indigenous languages. Colonization impacts were of critical concern and in need of undoing. Sharing of social and political efforts is seen as pivotal to change and includes all members of communities.